2015
DOI: 10.1214/15-aoas809
|View full text |Cite
|
Sign up to set email alerts
|

Sex, lies and self-reported counts: Bayesian mixture models for heaping in longitudinal count data via birth–death processes

Abstract: Surveys often ask respondents to report non-negative counts, but respondents may misremember or round to a nearby multiple of 5 or 10. This phenomenon is called heaping, and the error inherent in heaped self-reported numbers can bias estimation. Heaped data may be collected cross-sectionally or longitudinally and there may be covariates that complicate the inferential task. Heaping is a well-known issue in many survey settings, and inference for heaped data is an important statistical problem. We propose a nov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…In addition, the current study adopted a mixed method that used a logit model for the inflated probabilities without further elaborating the mechanism of inflation. Previous studies have shown that the inflation or heaping on certain values may be due to rounding to nearby popular values (Crawford et al, 2015;Wang & Heitjan, 2008). We hope that the current work can stimulate further developments that incorporate various measurement models.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, the current study adopted a mixed method that used a logit model for the inflated probabilities without further elaborating the mechanism of inflation. Previous studies have shown that the inflation or heaping on certain values may be due to rounding to nearby popular values (Crawford et al, 2015;Wang & Heitjan, 2008). We hope that the current work can stimulate further developments that incorporate various measurement models.…”
Section: Resultsmentioning
confidence: 74%
“…Data inflation may take various forms. It could be that respondents forget the information, or round to a nearby number of convenience (Crawford, Weiss, & Suchard, 2015); it can also be the result of hiding one's ignorance in situations where face-saving is deemed important (Bagozzi & Mukherjee, 2012). In other scenarios, measures on counts or summarized items, e.g., the number of hospital visits and the delinquency scale, may naturally concentrate on values of zero, or low occurrences such as one or two.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Heitjan (2008) proposed a model for heaped cigerate counts. A recent work of Crawford et al (2014) formulated a general model for count data involving birth-death processes and applied this to the self-reported counts of the number of sex-partners. In addition, Bar and Lillard (2012) lately developed an approach for event time data by modeling the density by a mixture of two parametric distributions.…”
Section: Heaping Models In Applicationsmentioning
confidence: 99%
“…Both applications indicated that these assumptions are not completely fullfilled in real-world data. As Crawford et al (2014) remarks, the assumption that, for example, a reported value of W i = 100 with rounding value R i = 10 means that the true unobserved value X i lies inside the interval (95,105) is rather strong. A possible solution would be to decompose the reporting process into an recall error (i.e.…”
Section: Simulation Studymentioning
confidence: 99%
“…A further source of error that is present is rounding or heaping (Crawford, Weiss and Suchard, 2015). From Table 1 there is clear evidence that the number casualties have been rounded to the nearest five: for the Native American's there were 69 and 51 events where the number of casualties was 4 and 6 respectively, whereas there were 126 recorded conflicts where the number of casualties was 5.…”
mentioning
confidence: 99%